2015
DOI: 10.1371/journal.pone.0130313
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Is a Novel Regulator of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Activity

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) attenuates sphingosine-1-phosphate (S1P) signaling in resistance arteries and has emerged as a prominent regulator of myogenic vasoconstriction. This investigation demonstrates that S1P inhibits CFTR activity via adenosine monophosphate-activated kinase (AMPK), establishing a potential feedback link. In Baby Hamster Kidney (BHK) cells expressing wild-type human CFTR, S1P (1μmol/L) attenuates forskolin-stimulated, CFTR-dependent iodide efflux. S1P’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 42 publications
(76 reference statements)
2
32
0
Order By: Relevance
“…1). 59,63 In the context of CF airways pathology, new interest has recently emerged for S1P as regulator of CFTR activity, 64 as well as from the intriguing relationship between altered S1P content and inflammatory response to bacterial infection. 52 The involvement of S1P in CF pathology is supported by evidence that inhibition of S1P degradation is associated with decreased lung inflammatory response to P. aeruginosa in a CF mouse model.…”
Section: Sphingosine and Sphingosine-1-phosphatementioning
confidence: 99%
“…1). 59,63 In the context of CF airways pathology, new interest has recently emerged for S1P as regulator of CFTR activity, 64 as well as from the intriguing relationship between altered S1P content and inflammatory response to bacterial infection. 52 The involvement of S1P in CF pathology is supported by evidence that inhibition of S1P degradation is associated with decreased lung inflammatory response to P. aeruginosa in a CF mouse model.…”
Section: Sphingosine and Sphingosine-1-phosphatementioning
confidence: 99%
“…(10) S1P and S1PRs have been shown to have differential roles in the regulation of cell proliferation, migration, and survival in different tissues and cells. (11)(12)(13)(14) It has been reported that S1P/S1PR3 signaling is involved in cholestasis-induced liver fibrosis (LF) (15) and S1P mediates bone-marrowderived macrophage migration through activation of S1PR2 and S1PR3 in the bile duct ligation (BDL) mouse model. (16) In addition, antagonism of S1PR2 selectively reduces portal vein pressure in BDL rodents.…”
mentioning
confidence: 99%
“…In recent years, much effort has been directed toward discovery and development of novel small molecule therapies for CF patients bearing the F508del and G551D mutations, since these mutations capture a large fraction of the patient population. [9][10][11][12][13] Accordingly, 2 small molecule therapies (Kalydeco ® , comprised of the potentiator ivacaftor or VX-770, and Orkambi ® , comprised of ivacaftor and the corrector lumacaftor or VX-809) have been developed for individuals with these mutations (G551D and F508del, respectively), as well as for those having a few other mutations with similar CFTR protein defects. 14,15 However, these discoveries as well as most other investigations typically explore CFTR mutations on a case-by-case basis, and do not consider the global mutation landscape as a whole.…”
mentioning
confidence: 99%